Expansion and structural change higher education in Germany, the United States, and Japan, 1870 - 1990 - Windolf, Paul 1946- (Westview Press, 1997)
As a central institution that ensures equality of opportunity and social justice, the university is the most important channel of social mobility in modern societies. Over the past century, universities have assumed an important role in the political and cultural emancipation of women, minorities, and the lower socioeconomic classes. Expansion and Structural Change explores this development, focusing on the social background of students and the institutional transformation of higher education in several countries. Who have been the beneficiaries of this remarkable process of educational expansion? Has it made Western society more open, mobile, and democratic? These questions are analyzed from a historical perspective that takes into account the institutional change of universities during this century